2019
DOI: 10.1155/2019/7915813
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Er:YAG Laser for Women with Stress Urinary Incontinence

Abstract: Purpose The aim of our study is to assess efficacy of noninvasive erbium-doped yttrium aluminium garnet laser (Er:YAG laser) for female stress urinary incontinence (SUI). Materials and Methods Forty-one women with SUI were included in the study and scheduled for vaginal Er:YAG laser treatment. The procedure was performed with a 2940 nm, Er:YAG laser (Fotona Smooth ™ XS, Fotona, Ljubljana, Slovenia), designed to heat up the vaginal mucosa to around 60°C. All subjects had a baseline and 6 months' posttreatment a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(66 citation statements)
references
References 34 publications
3
63
0
Order By: Relevance
“…Targeted conditions encompass symptomatic ectopic cervix 13 , lichen sclerosis at vulvovaginal 14 , vesicovaginal fistula 15 , pelvic organ prolapse 16 , 17 , ovarian function rejuvenation 18 , endometrial receptivity 19 , female sexual dysfunction 12 , membrane sealant in preterm pre-labor ruptured membrane 20 and cesarean section wound aesthetics 21 . We ever reported that the treatment efficacy for the vaginal Er:YAG laser for SUI at 6-month follow-up was 75.5% 22 . Promising impact of PRP and carbon dioxide laser for SUI was also noted recently 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Targeted conditions encompass symptomatic ectopic cervix 13 , lichen sclerosis at vulvovaginal 14 , vesicovaginal fistula 15 , pelvic organ prolapse 16 , 17 , ovarian function rejuvenation 18 , endometrial receptivity 19 , female sexual dysfunction 12 , membrane sealant in preterm pre-labor ruptured membrane 20 and cesarean section wound aesthetics 21 . We ever reported that the treatment efficacy for the vaginal Er:YAG laser for SUI at 6-month follow-up was 75.5% 22 . Promising impact of PRP and carbon dioxide laser for SUI was also noted recently 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Also ICIQ-UI SF and Australian PelvicFloor Questionnaire (APFQ) scores remained significantly lower at 1-year follow up: P = 0.001, 33 respectively. Six other studies with SUI as the primary diagnosis reported cure rates ranging from 38.1% to 75.5% at 6 months of follow up 24,32,47,48 and age, baseline ICIQ-UI SF values and body mass index as significant predictors of Rx efficacy. 27,49 No differences between laser types were observed.…”
Section: Urinary Incontinencementioning
confidence: 98%
“…26 Several studies on women with SUI included women with POP grade II, but only one cohort study reported subjective improvement in POPDI6 scores 6 months after three applications (P < 0.001). 48…”
Section: Pelvic Organ Prolapsementioning
confidence: 99%
See 1 more Smart Citation
“…[ 5 7 ] Epidemiological studies have showed that the prevalence rates of PPUI vary from 3% to 34%, [ 8 , 9 ] nearly 73% of women suffered from PPUI were still reported to have persistent urinary incontinence symptom even 6 years after giving birth. [ 10 ] In previous survey in middle-aged and old women in China, we even revealed that 40% women with PPUI would suffer from urinary incontinence in the future. [ 11 ] Obviously, PPUI has been raised as a significant public health problem, and therefore, it is reasonable for us to validate an effective approach for PPUI, to improve the life quality of patients.…”
Section: Introductionmentioning
confidence: 95%